Building and enhancing new literacies across the curriculum - Alata, Elen Joy P.; Ignacio, Eigen John T. (Manila : Rex Book Store, 2019)
Building and enhancing new literacies across the curriculum introduces the concepts of new literacies in the 21st century as an evolving social phenomenon and shared cultural practices across learning areas.
Chapter 1 Introduction to 21st century literacies 1 -- Chapter 2 Globalization and cultural and multicultural literacies 13 -- Chapter 3 Social literacy 35 -- Chapter 4 Financial literacy 47 -- Chapter 5 Media and cyber or digital literacies -- Chapter 6 Ecological literacy 79 -- Chapter 7 Artistic and creative literacy 91 -- Chapter 8 Critical literacy 103
Includes bibliographical references and index.
Keywords: LITERACY